SWORN TRANSLATION OF CHINESE NOTARIAL CERTIFICATES - WANG, Karolina (Comparative Legilinguistics, 2015)
This article discusses the translation of Chinese notarial certificates from the perspective of sworn translation. Given the challenges of legal translation in general and sworn translation in particular, the issue in question calls for clearly established translation criteria. The author decided to adopt the recommendations included in The Sworn Translator’s Code, issued by The Polish Society of Sworn and Specialized Translators, and Adequacy Conditions proposed by Roberto Mayoral (2000, 9-11). The analysis of Chinese notarial certificates focuses on the formal requirements of sworn translation, stylistic adequacy and the transliteration rules for Chinese personal names and addresses.